Order Monotonic Solutions for Generalized Characteristic Functions - René van den Brink; Enrique González-Aranguena; Conrado Manuel; Mónica del Pozo (Tinbergen Institute, 2013)
Generalized characteristic functions extend characteristic functions of 'classical' TU-games by assigning a real number to every ordered coalition being a permutation of any subset of the player set. Such generalized characteristic functions can be applied when the earnings or costs of cooperation among a set of players depends on the order in which the players enter a coalition. In the literature, the two main solutions for generalized characteristic functions are the one of Nowak and Radzik (1994), shortly called NR-value, and the one introduced by Sanchez and Bergantinos (1997), shortly called SB-value. In this paper, we introduce the axiom of order monotonicity with respect to the order of the players in a unanimity coalition, requiring that players who enter earlier should get not more in the corresponding (ordered) unanimity game than players who enter later. We propose several classes of order monotonic solutions for generalized characteristic functions that contain the NR-value and SB-value as special (extreme) cases. We also provide axiomatizations of these classes.
Keywords: C71; 330; Cooperative TU-game; generalized characteristic function; order monotonicity; Kooperatives Spiel; Transferable Utility Games